Gender, rhetoric and regulation : women's work in the Civil Service and the London County Council, 1900-55 / Helen Glew. - Glew, Helen (Gender in history., 2020)
Helen Glew investigates women's employment in the British Civil Service and London County Council during the 20th century, providing a new perspective on the development of the women's movement.